2008
DOI: 10.2169/internalmedicine.47.0316
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging in a Patient with Peripartum Cardiomyopathy

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…[195][196][197][198] The use of gadolinium during a cardiac MRI is not recommended during pregnancy. 199 Although MRI can be useful in evaluating chamber size and function and determining the presence of LV thrombus, the role of cardiac MR in predicting recovery potential remains uncertain, and data are limited.…”
Section: E594mentioning
confidence: 99%
“…[195][196][197][198] The use of gadolinium during a cardiac MRI is not recommended during pregnancy. 199 Although MRI can be useful in evaluating chamber size and function and determining the presence of LV thrombus, the role of cardiac MR in predicting recovery potential remains uncertain, and data are limited.…”
Section: E594mentioning
confidence: 99%
“…In PPCM, cardiac MRI provides more accurate quantification of chamber volumes and ventricular function, and is more sensitive in detecting LV thrombus than echocardiography (Mouquet, 2008;Srichai, 2006). At the present time, there are four case series with PPCM assessed by cardiac MRI (CaballeroBorrego, 2008;Kawano, 2008;Leurent, 2009;Mouquet, 2008). In only two of these studies the technique revealed myocardial inflammation.…”
Section: Investigation Of Peripartum Cardiomyopathymentioning
confidence: 93%
“…The interest for the technique is also suggested by the ability to differentiate PPCM from other forms of cardiomyopathy, like Tako-Tsubo or ischemic cardiomyopathy. The technique might be a useful method for guiding biopsy to the abnormal area (Leurent et al, 2009), and for prognostic stratification (Kawano et al, 2008). In his comment, Fett supports cardiac MRI for PPCM which is not responding to conventional therapy as long as late gadolinium enhancement is more likely to be present in these cases (Fett, 2009).…”
Section: Investigation Of Peripartum Cardiomyopathymentioning
confidence: 98%
“…(88) Some evidence exists for the usefulness of MRI for diagnosis, pathogenic and prognostic consideration in patients with PPCM. (89) Cardiac catheterisation can be used for evaluation of left ventricular function, obtaining endomyocardial biopsies and performing coronary angiography, but is not essential to diagnosis in most cases.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%